(untitled) (Лучшие интеллектуальные исследования, 2024)
The final design of the new Basel IV: Standardized Measurement Approach (SMA) is less conservative than proposed in the consultation paper—however, the impact on capital requirements will, for some banks, still be severe. • Final approach • Capital impacts • Need for action • Summary The Basel Committee on Banking Supervision (BCBS) has finalized the Standardized Approach (SMA) for calculating the capital charges for operational risk.[1] Compared to the consultation paper, the approach has mainly stayed the same: the SMA consists of the two components Business Indicator Component (BIC) and Internal Loss Multiplier (ILM for short), which are multiplied by each other.[2]